2020
DOI: 10.5811/westjem.2020.4.47475
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Extubations Performed in an Emergency Department-based Intensive Care Unit

Abstract: Extubation of appropriate patients in the emergency department (ED) may be a strategy to avoid preventable or short-stay intensive care unit (ICU) admissions, and could allow for increased ventilator and ICU bed availability when demand outweighs supply. Extubation is infrequently performed in the ED, and a paucity of outcome data exists. Our objective was to descriptively analyze characteristics and outcomes of patients extubated in an ED-ICU setting. Methods: We conducted a retrospective observational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Multiple recent studies have demonstrated benefits of ED‐ICUs, including observed reduction in mortality, reduction in rates of ICU admission or hospitalization, and reductions in hospital LOS. 18 , 19 , 26 , 27 , 28 , 29 , 30 Centers with high rates of ED boarding of patients who are critically ill and those considering implementing an ED‐ICU can consider these findings in the context of their individual practice environments to best mitigate detrimental effects of ED boarding of patients who are critically ill on the local scale. With increasing numbers of ED‐ICUs and more centers considering implementing similar units, continued assessment of outcomes (including prospective research) to guide further development is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent studies have demonstrated benefits of ED‐ICUs, including observed reduction in mortality, reduction in rates of ICU admission or hospitalization, and reductions in hospital LOS. 18 , 19 , 26 , 27 , 28 , 29 , 30 Centers with high rates of ED boarding of patients who are critically ill and those considering implementing an ED‐ICU can consider these findings in the context of their individual practice environments to best mitigate detrimental effects of ED boarding of patients who are critically ill on the local scale. With increasing numbers of ED‐ICUs and more centers considering implementing similar units, continued assessment of outcomes (including prospective research) to guide further development is essential.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, as focus is shifting from proving the benefit of LPV to proving it can be implemented and adhered to, an ED-ICU is one strategy to increase LPV adherence (39). Additionally, these findings add to the robust patient and resource utilization outcomes in other common disease states associated with an ED-ICU (26)(27)(28)(29)(30)(31). Health systems may consider these results when determining the feasibility of ED-ICU implementation and future work should examine outcomes associated with ED-ICUs at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…To combat this and to optimize early delivery of high-quality critical care, ED-based ICUs (also known as Resuscitative Care Units) have been implemented at a small number of institutions across the United States (25). In other disease processes, an ED-ICU has been associated with improved outcomes, including decreased mortality, inpatient ICU admission, and resource utilization (15,(26)(27)(28)(29)(30)(31). There are no prior investigations on the impact of an ED-ICU on adherence to LPV for ED patients receiving mechanical ventilation.…”
mentioning
confidence: 99%
“…13 Patients in the ED requiring ongoing critical care can be transferred to EC3 regardless of inpatient ICU bed availability, and common indications for transfer have been previously described. 13 The ED-ICU model has previously been associated with improved patient mortality and reduced ICU use [13][14][15][16][17]…”
Section: Importancementioning
confidence: 99%
“…Patients in the ED requiring ongoing critical care can be transferred to EC3 regardless of inpatient ICU bed availability, and common indications for transfer have been previously described 13 . The ED‐ICU model has previously been associated with improved patient mortality and reduced ICU use 13–17 and may offer an opportunity to reduce ICU admissions among patients receiving end‐of‐life care or for whom ICU admission is not in alignment with goals of care.…”
Section: Introductionmentioning
confidence: 99%